PEMBERDAYAAN MASYARAKAT MELALUI RELAKSASI OTOT PROGRESIF TERHADAP PENGETAHUAN, SIKAP, KETERAMPILAN, DAN GEJALA GERD - Revani, Hilda Dea; Erindia, Firnanda; Orizani, Chindy Maria (PPM STIKES Adi Husada, 2026)
Introduction & Objectives: Community service through Progressive Muscle Relaxation Therapy in the Donokerto I Area, Kapasan Village, Simokerto Subdistrict, was motivated by the high prevalence of Gastroesophageal Reflux Disease (GERD), which is characterized by gastric acid reflux and causes symptoms such as epigastric pain and a reduced quality of life. Stress is known to exacerbate symptoms through increased visceral sensitivity and gastric acid secretion. This community service, through progressive muscle relaxation therapy, is used to manage GERD symptoms. Methods: Community service used a health education approach combined with demonstrations of progressive muscle relaxation techniques. Implementation methods included lectures, discussions, and hands-on practice sessions for participants. Evaluation utilized a pre-test and post-test design to measure knowledge improvement, attitude, and observation of symptom changes using the GERD Questionnaire. The participants consisted of 21 adults with GERD. Results: The results showed an increase in participants’ knowledge and attitudes regarding GERD, and in their skill in progressive muscle relaxation techniques following the activity. Additionally, some participants reported a reduction in the intensity of symptoms such as heartburn, burning, and muscle tension. Discussion: Progressive muscle relaxation is effective as a complementary therapy in helping manage GERD symptoms, although its success depends heavily on regular and sustained practice.